2012
DOI: 10.1016/j.bbadis.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA deletions and differential mitochondrial DNA content in Rhesus monkeys: Implications for aging

Abstract: The purpose of this study was to determine the relationship between mitochondrial DNA (mtDNA) deletions, mtDNA content and aging in rhesus monkeys. Using 2 sets of specific primers, we amplified an 8 kb mtDNA fragment covering a common 5.7 kb deletion and the entire 16.5 kb mitochondrial genome in the brain and buffy-coats of young and aged monkeys. We studied a total of 66 DNA samples: 39 were prepared from a buffy-coat and 27 were prepared from occipital cortex tissues. The mtDNA data were assessed using a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…To understand the mechanisms of aging, particularly the role of mtDNA in the brain, several researchers studied mtDNA, free radical production, and mitochondrial function in young and aged tissues from rodents, nonhuman primates, and humans [reviewed in 5, 7, 18, 19, 23 and 29, 30]. In aged tissues relative to young tissues from rodents, nonhuman primates, and humans, researchers found an accumulation of mtDNA defects, an increased production of ROS, and decreased mitochondrial function in the brain tissues from old rodents, nonhuman primates and humans [7, 18, 19, 29, 30], indicating that age-related accumulation of mtDNA defects is involved in aging. It has been reported that mitochondrial ETC is responsible for the transfer of electrons from NADH or FADH, to electron acceptors, and to oxygen, the final transfer of which leads to the production of H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanisms of aging, particularly the role of mtDNA in the brain, several researchers studied mtDNA, free radical production, and mitochondrial function in young and aged tissues from rodents, nonhuman primates, and humans [reviewed in 5, 7, 18, 19, 23 and 29, 30]. In aged tissues relative to young tissues from rodents, nonhuman primates, and humans, researchers found an accumulation of mtDNA defects, an increased production of ROS, and decreased mitochondrial function in the brain tissues from old rodents, nonhuman primates and humans [7, 18, 19, 29, 30], indicating that age-related accumulation of mtDNA defects is involved in aging. It has been reported that mitochondrial ETC is responsible for the transfer of electrons from NADH or FADH, to electron acceptors, and to oxygen, the final transfer of which leads to the production of H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between the mtDNA 4,977-bp common deletion load in the brain and neuropsychiatric disorders have also been reported [8,9,10,11]. The mtDNA common deletion levels have been shown to increase in the brain with advanced aging [12,13]. However, we have previously observed that the age-related increase in the common deletion in brain was significant in control subjects but was not observed in SZ [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive response would partially compensate for mitochondrial dysfunction in these neurodegenerative diseases and would afford a human evolutionary response to shortage of ATP in the frontal cortex. This compensation also can be found in the brain of aged non-human primates [63].…”
Section: Definition and Pathology Of Dementia Withmentioning
confidence: 70%